Complejo de capacitación y tecnificación agrícola del Guaviare (2020)
The project begins with an analysis of the department of Guaviare and the municipalities that compose it (San José del Guaviare, El Retorno, Calamar and Miraflores) highlighting its natural and cultural values, showing a problem due to the lack of infrastructure, illicit crops and presence of armed groups because of this. The municipality of the return has the majority of its population located in the rural area, which focuses agricultural production in this sector and leaves the populated center of the municipality unrelated due to lack of infrastructure. For the partial plan, a proposal is presented to connect rural centers to improve the economy of both the municipality and the region, promoting the industrial sector and implementing a training complex where the inhabitants of the region can learn new techniques for implementing the native crops of the region, giving added value and strengthening the educational and productive sector of the region.